Karnataka Development Report - Planning Commission (Planning Commission, 2007)
In the Golden Jubilee year of the formation of the Karnataka State this is considered to be most appropriate and privilege to bring out a Status Report on development in Karnataka. To begin with the Planning Commission and the Planning Department, Government of Karnataka approached the Institute for Social and Economic Change (ISEC) to act as a Nodal Agency to prepare the Karnataka Development Report.
Planning Commission Government of India
Planning Commission Government of India